Parental life satisfaction based on parenting myths - Mehrangiz Shoaa Kazemi; Seiedeh Narjes Emrani (Gonabad University of Medical Sciences, 2019)
Parents' beliefs and attitudes about parenting have a significant effect on their life satisfaction. The purpose of this study was to assess the satisfaction with life in parents based on parental myths of Iranian parents. To examine the parental myths, two questionnaires of Seidi's parenting myth with 69 questions and Kansas family life satisfaction with 4 items were used. Inferential statistics (multivariate regression) were used to analyze the data. The results showed that there wasa significant relationship between parenting myths and life satisfaction. In the best-of-breed prediction model for satisfying the lives of parents, the excessively calm parenting, efficacy, and pre-marriage-behavioral myths were able to predict the criterion variable. Excessively calm parenting myth contributed mostly to life satisfaction. The myth of pre-marriage-behavioral was also a negative predictor of life satisfaction. In sum, the results of this study showed that although parental myths seem to cause physical fatigue inIranian parents, in Iranian society, the level of satisfaction with life was high despite the efforts to improve the effective education of children.